Unusual presentation of intravascular papillary endothelial hyperplasia (Masson's tumor) - Marco Breccia, MD; Mariangela Novello, MD; Marco Galli, MD; Antonella Coli (Elsevier, 2015)
Intravascular papillary endothelial hyperplasia is a rare, exuberant form of reactive endothelial proliferation which can mimic benign and malignant vascular tumors. In this report, we describe a 22-year-old man presenting with a 2.5 cm nodule on his left foot, near the first metatarsal head. The patient underwent total excision of the lesion, with subsequent histological diagnosis of intravascular papillary endothelial hyperplasia arising within a thrombosed periosteal vein. After nine months from surgery, the patient is alive and well, with no evidence of local recurrence.